2020
DOI: 10.3390/app10217624
|View full text |Cite
|
Sign up to set email alerts
|

How Do Plants and Climatic Conditions Control Soil Properties in Hypersaline Tidal Flats?

Abstract: Hypersaline tidal flats (HTF) are ecotones associated with mangrove ecosystems in arid and semiarid coasts. They are predominantly vegetated by halophytes which are related to environmental stabilization and fauna protection. Some plants thrive in HTF by modifying soil biogeochemical conditions at their rhizospheres, expanding across barren soils. Thus, we aimed to study rhizospheric and the adjacent bulk soils of the three most abundant plant species in HTF under a seasonal semiarid climate of northeastern Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
(101 reference statements)
0
2
0
Order By: Relevance
“…Diverse studies have shown that soils of coastal wetlands (e.g., mangroves, salt marshes, and hypersaline tidal flats) can be very dynamic and spatially variable, resulting from an interaction between biotic (e.g., plant species and bioturbation; Araujo Juńior et al, 2012;Cabral et al, 2020), and abiotic factors (i.e., physiographic position, flooding frequency, geological bedrocks, and climate; Seybold et al, 2002;Du Laing et al, 2009;Albuquerque et al, 2014;Ferronato et al, 2016;Ferreira et al, 2022).…”
Section: Physicochemical Diversity Of Seagrass Meadows and Its Effect...mentioning
confidence: 99%
“…Diverse studies have shown that soils of coastal wetlands (e.g., mangroves, salt marshes, and hypersaline tidal flats) can be very dynamic and spatially variable, resulting from an interaction between biotic (e.g., plant species and bioturbation; Araujo Juńior et al, 2012;Cabral et al, 2020), and abiotic factors (i.e., physiographic position, flooding frequency, geological bedrocks, and climate; Seybold et al, 2002;Du Laing et al, 2009;Albuquerque et al, 2014;Ferronato et al, 2016;Ferreira et al, 2022).…”
Section: Physicochemical Diversity Of Seagrass Meadows and Its Effect...mentioning
confidence: 99%
“…Soils are classified as saline when the ECe is 4 dS m −1 or more [7], equivalent to approximately 40 mM or 2.3 g L −1 NaCl. In this scenario, the continuous increase in salinisation (and sodification) transforms saline areas into hypersaline ones, which are extreme environments where the salinity is very high (similar or higher than that of seawater, 35-40 g L −1 NaCl or 600-680 mM), where plant growth is strongly limited and may be suitable for halophytes only [8][9][10].…”
Section: Introductionmentioning
confidence: 99%